Simplifique a expressão
para x
+ - 5.
Soluções para a tarefa
Respondido por
46
3x² + 30x + 75
x² - 25
3.(x² + 10x + 25)
x² - 25
3.(x + 5) . (x + 5) elimina (x + 5)
(x - 5) . (x + 5) elimina( x + 5)
3.(x + 5)
(x - 5)
3(x + 5)
x - 5
x² - 25
3.(x² + 10x + 25)
x² - 25
3.(x + 5) . (x + 5) elimina (x + 5)
(x - 5) . (x + 5) elimina( x + 5)
3.(x + 5)
(x - 5)
3(x + 5)
x - 5
VictoriaRuffo:
resposta final?
Respondido por
9
Resolvendo o numerador:
3x² + 30x+ 75= (:3)
x² + 10x + 25 =
(x + 5)²
Resolvendo o denominador:
x² - 25 = (x-5)(x+5)
Fica assim:
![\frac{(x+5)^2}{(x+5)(x-5)} -->simplificando \frac{(x+5)^2}{(x+5)(x-5)} -->simplificando](https://tex.z-dn.net/?f=+%5Cfrac%7B%28x%2B5%29%5E2%7D%7B%28x%2B5%29%28x-5%29%7D+--%26gt%3Bsimplificando)
=
![\frac{3(x+5)}{x-5} \frac{3(x+5)}{x-5}](https://tex.z-dn.net/?f=+%5Cfrac%7B3%28x%2B5%29%7D%7Bx-5%7D+)
3x² + 30x+ 75= (:3)
x² + 10x + 25 =
(x + 5)²
Resolvendo o denominador:
x² - 25 = (x-5)(x+5)
Fica assim:
Perguntas interessantes